Design and Simulation of Airfield Lighting System Using 8 Luminaire in Airfield Lighting Laboratory at Politeknik Penerbangan Surabaya. Issue 1 (March 2021) - Sudjoko, R I; Hartono,; Hariyadi, S; Suwito,
Abstract: Airfield lighting system (ALS) provides visual reference to aircrafts during airport operation. In ALS equipment, constant current regulator (CCR) feed a luminaire circuit supplied through isolation transformer. Luminaire circuits are a large number of lamps which organized in serial circuit and connected to CCR that supply energy to the lamps. Modeling the component is needed to simulate ALS including of constant current regulator, underground cables, isolation transformer, and lamps. This simulation is usefull to study ALS behaviour and predict their response to electrical systems and future technological changes. This paper present circuit design and simulation of ALS using power simulator (Psim) software. The simulation results are observed in maximum brightness condition of the CCR. The CCR measurement results for this condition are 6.63 Ampere current output and 5kV voltage output. It has been observed that the designed system has been succesfully implemented to airfield lighting system circuit according to the component specification.